Validation of the 2019 EULAR/ACR classification criteria for systemic lupus erythematosus in an academic tertiary care centre - Arndt Weinmann; Julia Weinmann-Menke; Irene Schmidtmann; Daniel Kraus; Katharina Pütz; Paul Claßen; Eva Maria Schleicher; Simone Cosima Boedecker-Lips (RMD Open, 2023)
Objectives To assess the sensitivity and specificity of the 2019 EULAR/American College of Rheumatology (ACR) classification criteria for systemic lupus erythematosus (SLE) in outpatients at an academic tertiary care centre and to compare them to the 1997 ACR and the 2012 Systemic Lupus International Collaborating Clinics criteria.Methods Prospective and retrospective observational cohort study.Results 3377 patients were included: 606 with SLE, 1015 with non-SLE autoimmune-mediated rheumatic diseases (ARD) and 1756 with non-ARD diseases (hepatocellular carcinoma, primary biliary cirrhosis, autoimmune hepatitis). The 2019 criteria were more sensitive than the 1997 criteria (87.0% vs 81.8%), but less specific (98.1% vs 99.5% in the entire cohort and 96.5% vs 98.8% in patients with non-SLE ARD), resulting in Youden Indexes for patients with SLE/non-SLE ARD of 0.835 and 0.806, respectively. The most sensitive items were history of antinuclear antibody (ANA) positivity and detection of anti-double-stranded deoxyribonucleic acid (dsDNA) antibodies. These were also the least specific items. The most specific items were class III/IV lupus nephritis and the combination of low C3 and low C4 complement levels, followed by class II/V lupus nephritis, either low C3 or low C4 complement levels, delirium and psychosis, when these were not attributable to non-SLE causes.Conclusions In this cohort from an independent academic medical centre, the sensitivity and specificity of the 2019 lupus classification criteria were confirmed. Overall agreement of the 1997 and the 2019 criteria was very good.